The educational context of the Sejm protest by people with disabilities and their families - BEŁZA-GAJDZICA, MAGDALENA; GAJDZICA, ZENON (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Magdalena Bełza-Gajdzica, Zenon Gajdzica, The educational context of the Sejm protest by people with disabilities and their families. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 83-103. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.04 This paper presents an analysis of the social reception of a protest by people with disabilities and their families (and guardians), with a special focus on its educational dimension. The protest took place in the main corridor of the Sejm complex in Warsaw in April and May 2017. The first part of the paper comprises the essential characteristics of social protests. The second provides a brief overview of media information about the discussed protest. The recapitulation of this part specifies the conditions that give the protest an educational dimension. From there, the analysis is narrowed to the reception of knowledge pertaining to the situation of the needs of people with disabilities and their families and the change in attitudes to this social group. The third part comprises a presentation of the research results on this issue. The research was conducted with the use of diagnostic polling—the questionnaire technique, applied to a group of 200 people. The research results show that the protest was a kind of information campaign and that it contributed to some changes in respondents’ knowledge concerning people with disabilities and their families and the transformation of attitudes to their needs.